The Public Sphere, Inclusion and Algorithms, or the Communicative Rationality of Jürgen Habermas in the Context of Algorithmic Exclusion in Social Media - Filipiak, Magdalena (Sensus Historiae, 2022)
The article aims to analyze the public sphere and the rationality of communication according to Jürgen Habermas in the context of the functioning of social media. The content filtering mechanisms available to social media users raise doubts as regards the fulfilment of Habermas’s inclusiveness. Communicative rationality should counteract social polarization and discursively resolve emerging conflicts. From the popular point of view, social media is a place of free and unrestricted communication, inclusion, access to diverse opinions and pluralism. These features of social media express hope for the realization of the public sphere and emancipation, which is enabled by the rationality inherent in the very language and principles of communication. However, the main barrier to implementing the public sphere is the algorithms and recommendation systems that filter the content presented to users. A hazardous phenomenon is an algorithmic bias, which has a real impact on people's lives.